Acanthamoeba spp. genotypes demonstrate genotype-specific motility and encystment differences in both fed and starved environments - Campolo, Allison; Lara, Esther; Crary, Monica (Frontiers in Ophthalmology, 2025)
IntroductionAcanthamoeba is a ubiquitous protozoan pathogen that can cause a severe ocular infection, Acanthamoeba keratitis. Despite its high prevalence and potential contamination of contact lenses, the natural behavior of this parasite remains poorly understood. Therefore, we investigated Acanthamoeba trophozoite movement, rate of encystment, trophozoite size, and phylogenetic relationships between eight prevalent Acanthamoeba genotypes.MethodsAcanthamoeba was seeded onto a plate with and without E. coli. After initial size measurements were recorded, images were taken using a microscope to create time-lapse videos over a 72-hour period. Amoeba trophozoite tracks were quantified for distance, displacement, and speed. Separately, Acanthamoeba cysts were generated naturally over the course of the study via nutrient deprivation in ¼ Ringer’s over 72 hours. Wells were stained with calcofluor white to identify cysts and wells were quantified for rate of encystment and cyst size.ResultsOf the eight genotypes investigated, T7 and T18 possessed the largest trophozoite size while T5 was the smallest. T5 was consistently the fastest genotype over the 72-hour period in both the fed and starved conditions. Nutrient conditions did not show any consistent impact on the overall distance, speed, or encystment of any genotype within 72 hours. Finally, while some genotypes (T1, T11) demonstrated a relatively high percentage of encystment at the 24-, 48-, and 72-hour timepoints, the other genotypes demonstrated a relatively low encystment percentage at these same times.DiscussionOverall, these results indicate that eight of the common genotypes of Acanthamoeba vary widely in terms of size, speed, rates of encystment, and response to nutritional state. From these, we can infer that Acanthamoeba keratitis prevention methods must be robust enough to counter amoeba in trophozoite or cyst form, and that amoeba should be expected to be able to traverse a wide variety of distances (for instance, across a contact lens or onto a corneal epithelium) in either a fed or starved nutritional state.